2021
DOI: 10.1111/sltb.12697
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeper training needs of community pharmacy staff

Abstract: Objective To develop an online suicide prevention gatekeeper training program to prepare community pharmacy staff to communicate with patients who exhibit warning signs of suicide. Method A convenience sample of 17 community pharmacy staff members completed a 1‐hr semi‐structured interview during which they viewed content from an existing gatekeeper training program and provided suggestions for improvement. Once thematic saturation was achieved, interviews were digitally recorded, transcribed, and analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 18 publications
(35 reference statements)
1
37
0
Order By: Relevance
“…A Washington State survey assessing pharmacy students’ confidence, knowledge, and skills in suicide prevention pre- and post-training reported their increased confidence and skills in recognising suicide warning signs and their ability to have an emotional connection and intervene [ 38 ], supporting all the studies that have been identified in this commentary [ 7 , 11 , 12 , 25 , 33 ].…”
Section: Facilitators For Community Pharmacists’ Involvement In Suici...supporting
confidence: 57%
See 3 more Smart Citations
“…A Washington State survey assessing pharmacy students’ confidence, knowledge, and skills in suicide prevention pre- and post-training reported their increased confidence and skills in recognising suicide warning signs and their ability to have an emotional connection and intervene [ 38 ], supporting all the studies that have been identified in this commentary [ 7 , 11 , 12 , 25 , 33 ].…”
Section: Facilitators For Community Pharmacists’ Involvement In Suici...supporting
confidence: 57%
“…As stated previously, community pharmacists could have a significant role in suicide prevention through pharmacist–patient interaction and medication management, which is classified as restricting access to means [ 7 ]. Furthermore, community pharmacists could be a link to other healthcare systems in terms of referral and triage [ 12 , 25 ].…”
Section: Community Pharmacists’ Potential Role In Suicide Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected studies are characterized by their extreme heterogeneity in terms of study design, type and size of populations studied, their purpose, and outcomes. Of the 35 included studies, most of them were observational studies without a control group ( n = 22) [ 30 , 50 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], four were quasi-experimental prospective controlled studies [ 92 , 93 , 94 , 95 ], four were cross-sectional studies [ 96 , 97 , 98 , 99 ] and five were randomized control trials (RCTs) [ 18 , 100 , 101 , 102 , 103 ].…”
Section: Resultsmentioning
confidence: 99%